2019
DOI: 10.1177/0954410019829283
|View full text |Cite
|
Sign up to set email alerts
|

Sensor placement and moving horizon state/parameter estimation for flexible hypersonic vehicles

Abstract: Considering the nonlinearity, uncertainty, and rigid/elastic coupling, a state/parameter joint estimation method is essential for control system design or fault diagnosis of flexible hypersonic vehicles. With the goal of improving state/parameter estimation accuracy, this paper proposes a sensor placement strategy and a moving horizon estimation algorithm with a QR-decomposition-based arrival cost update strategy (MHE-QR). To enhance observability, a novel double sensor placement strategy, in which the sensor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 29 publications
(54 reference statements)
0
6
0
Order By: Relevance
“…Remark 10. Although Chen et al 36 have proved that the moving horizon estimator is stable, which is also demonstrated by the simulation results, the estimation error still exists. It is important that the estimation result of SMDO and the stability of control system are both affected by the estimation error of moving horizon estimator.…”
Section: Stability Analysismentioning
confidence: 91%
See 4 more Smart Citations
“…Remark 10. Although Chen et al 36 have proved that the moving horizon estimator is stable, which is also demonstrated by the simulation results, the estimation error still exists. It is important that the estimation result of SMDO and the stability of control system are both affected by the estimation error of moving horizon estimator.…”
Section: Stability Analysismentioning
confidence: 91%
“…Since the significant flexible effects are caused by the longitudinal bending of fuselage, 35 the structure of FHV is modeled as a freebeam. Under the assumption that the earth is flat, the longitudinal dynamics of FHV whose parameters are given in Chen et al 36 are as follows 14,37…”
Section: Dynamic Modelmentioning
confidence: 99%
See 3 more Smart Citations